2016
DOI: 10.5530/pc.2016.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Efficacy of Mimusops Elengi L. Flowers in Albino Wistar Rats using Excision Wound Model

Abstract: Introduction: Mimusops elengi L. (Sapotaceae), known as Bakul in Ayurveda, is an evergreen tree found throughout India. M. elengi flowers (MEF) are reported to possess immunomodulatory, hepatoprotective, skin whitening, anti-anxiety and wound healing activities which may be attributed to its phytochemical constituents including triterpenoids, alkaloids, phenolics, volatile oils, etc. Although the flowers have been traditionally used as a wound healing agent, there is a paucity of scientific data in support of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The results of this study showed that ointment‐treated wounds contract faster when compared to controls. The raised wound contraction rate in MZL‐ointment group could be due to an increase in fibroblasts proliferation and their transformation into myofibroblasts (Shailajan & Gurjar, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study showed that ointment‐treated wounds contract faster when compared to controls. The raised wound contraction rate in MZL‐ointment group could be due to an increase in fibroblasts proliferation and their transformation into myofibroblasts (Shailajan & Gurjar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wounds treated with the methanol extract of Z. lotus leaves showed significant ( p < .05) increase in hydroxyproline, hexosamines and proteins levels of the granulation tissue in comparison with control wounds (Table ). An increase in collagen content and stabilization of its fibers might be responsible for the increase in hydroxyproline concentration after application of the MZL‐ointment (Shailajan & Gurjar, ). Hexosamines are components of glycosaminoglycans which constitute the basis of the newly formed extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethanolic extracts of Chrysophyllum cainito and Mimusops elengi were standardized as previously reported. [11][12] The ointment of Chrysophyllum cainito and Mimusops elengi (each containing 20% ethanolic extract) was prepared as described previously. [11][12]19 Experimental design The protocol for pharmacokinetic study was approved by Institutional Animal Ethics Committee before commencement of the study (Approval No.…”
Section: Standardization Of the Extracts And Preparation Of The Test mentioning
confidence: 99%
“…Furthermore, the traditional claim on their wound healing potential was supported using excision wound rat model. [11][12] Therefore, in the present research work, the pharmacokinetic profile of the bioactive marker gallic acid was studied post topical application of the ointment containing ethanolic extract of Chrysophyllum cainito and Mimusops elengi in male Wistar rats using a validated HPLC method. To date, several studies on pharmacokinetics of gallic acid from different biological matrices using various experimental models have been reported.…”
Section: Introductionmentioning
confidence: 99%